BUENAS PRÁCTICAS EN LA AUTOEVALUACIÓN Y ACREDITACIÓN DE CARRERAS: LA EXPERIENCIA DE LA UNIVERSIDAD NACIONAL DE COSTA RICA (UNA) (Revista Electrónica Calidad en la Educación Superior, 2017)
El presente artículo es producto de un proceso reflexivo realizado por el personal académico de la Vicerrectoría de Docencia que gestiona  el seguimiento, evaluación y acreditación de carreras en la Universidad Nacional de Costa Rica (en adelante UNA), considerando  la experiencia,  madurez y aprendizajes, alcanzado en el transcurso de 16 años en procesos de autoevaluación con fines de acreditación que, al año 2016, se refleja en 20 carreras acreditadas.  Esto ha  permitido,  entre otros logros, institucionalizar buenas prácticas en tanto se consolidan como formas de actuar que promueven y potencian la cultura de evaluación y calidad en la UNA. Dichas prácticas refieren a:Asesoría, acompañamiento y capacitación permanentes.Incorporación de  estrategias de participación de personal académico,  administrativo y estudiantil,  liderado por autoridades de la carrera.Incorporación de la cultura evaluativa y de calidad en la planificación institucional.  GOOD PRACTICES IN PROCCES OF SELF-ASSESMENT AND ACREDITATION OF CAREERSTHE UNIVERSIDAD NACIONAL DE COSTA RICA (UNA)Summary The present article is the result of a reflective process done by the academic staff of the Vice-rectory of Teaching, which executes everything pertaining the follow up, evaluation and accreditation of careers in Universidad Nacional de Costa Rica (UNA), taking into consideration the input of the academics of the institution that have experience in the processes of careers auto-evaluations.  Such reflection is sustained by the maturity and knowledge achieved throughout 16 years of continuous practice in procedures of auto-evaluation, that to the year of 2016, reflects on 20 accredited careers.  This maturity has allowed among other achievements, to institutionalize practices and actions that we have named good practices, in the sense that they’re consolidated as ways to act that ease, promote and potentiate the culture of evaluation and quality in UNA. Such practices refer to:Assessment, monitoring and ongoing training that imply the consolidation of a team of academics in the Vice-rectory of Teaching.Strategies of participation inside the academic department and assignment of resources and time from a perspective of participative evaluation, promoting inside each academic department the intervention and involvement of the academic, administrative, and student personnel, led by the authorities of each career. Incorporation of the topic in the institutional politic and planning as such foundation contributes to the sustainability and consolidation of the evaluative and quality culture.Keywords: Good practices, Auto-evaluation, Improvement of the quality, Higher Education, Careers Accreditation.